Magnetic Properties Change in Street Dust in Baghdad City, Iraq - Ameen, Nawrass; Khwedim, Kareem (Iraqi Journal of Science, 2025)
The magnetic properties of street dust in the north and south of Baghdad, Iraq, have been studied. Fifty soil samples have been collected from heavily Traffic streets. Mass-specific magnetic susceptibility (χ), frequency-dependent susceptibility (χfd%), anhysteretic remanent magnetization (χarm), saturation isothermal remanent magnetization (SIRM), and thermomagnetic analyses were investigated. Mass-specific magnetic susceptibility (χ) is 72.86 × 10-8 m3kg-1 and 98.31 × 10-8 m3kg-1 for northern Baghdad (BN) and southern Baghdad (BR) (mean values), respectively. χ is well correlated with χarm with correlation coefficients (R2) of 0.96 and 0.83 for BN and BR, respectively. Grain size analyses show the existence of single-domain (SD) magnetite and maybe a small portion or absence of superparamagnetic (SP) grains in the samples. Thermomagnetic analyses clearly show a dramatic drop in the curve around 580°C during heating, which is the Curie temperature of magnetite. Results of concentration-dependent parameters, grain size, coercivity, and thermomagnetic analyses show the dominance of a soft magnetic phase like magnetite and the existence of a hard magnetic phase like hematite or goethite.